Teaching Algerian Third-Year Elementary-school Pupils English Vocabulary Through Songs: An Effective Instructional Tool to Enliven English Classes - Dallel Sarnou; Hanane Sarnou (Ignatianum University Press, 2023)
Research objectives (aims), issues or problems: The study accentuates the significant role that integrating songs into the teaching of English vocabulary has for third-year elementary-school pupils in Algeria. It aims to make English vocabulary acquisition effortless and fun for young learners and seeks to facilitate teaching English as a second foreign language for newly recruited instructors. In fact, a major query of this research concerns the incomprehensible lack of songs, poems, and nursery rhymes in the English textbook for third-year pupils, who are 8 to 9 years old, i.e., at an age when musical activities help them become motivated and interested in class activities. Research methods: To test the efficacy of songs in teaching English vocabulary to young third-year learners, the researchers opted for a true experimental research method. An experimental group of 26 pupils was exposed to nursery rhymes about numbers, colors, and family members, while a control group of 25 pupils was taught the same vocabulary items for three weeks using lessons from the textbook only. A short description of the context of the presented issue: The experiment took place in one of elementary schools in the city of Mostaganem, where the researchers' former student works as a teacher of English. The experiment lasted three weeks: from January 10 to January 31, 2023. Research findings: The findings of this research indicate that the use of songs considerably improved the average vocabulary scores for the 26 young pupils in the experimental group compared to the control group. Therefore, this research paper concludes that songs enhance natural and effortless vocabulary acquisition among third-year pupils who are learning English for the first time. Conclusions and/or recommendations: Moreover, this study encourages elementary-school English teachers to give more pedagogical consideration to the use of children's songs in teaching English to their pupils so as to enliven the lessons and to raise the pupils' motivation to learn this foreign language.